The Influence of End‐of‐Life Care on Organ Donor Potential. Issue 7 (2nd May 2017) - Witjes, M.; Kotsopoulos, A.; Herold, I.H.F.; Otterspoor, L.; Simons, K.S.; van Vliet, J.; de Blauw, M.; Festen, B.; Eijkenboom, J.J.A.; Jansen, N.E.; van der Hoeven, J.G.; Abdo, W.F.
Abstract : Many patients with acute devastating brain injury die outside intensive care units and could go unrecognized as potential organ donors. We conducted a prospective observational study in seven hospitals in the Netherlands to define the number of unrecognized potential organ donors outside intensive care units, and to identify the effect that end‐of‐life care has on organ donor potential. Records of all patients who died between January 2013 and March 2014 were reviewed. Patients were included if they died within 72 h after hospital admission outside the intensive care unit due to devastating brain injury, and fulfilled the criteria for organ donation. Physicians of included patients were interviewed using a standardized questionnaire regarding logistics and medical decisions related to end‐of‐life care. Of the 5170 patients screened, we found 72 additional potential organ donors outside intensive care units. Initiation of end‐of‐life care in acute settings and lack of knowledge and experience in organ donation practices outside intensive care units can result in under‐recognition of potential donors equivalent to 11–34% of the total pool of organ donors. Collaboration with the intensive care unit and adjusting the end‐of‐life path in these patients is required to increase the likelihood of organ donation. Abstract : Initiation of end‐of‐life care in acute settings, as well as lack of knowledge and experience in organ donation practices, results in underrecognition of patients who could be organ donors.